Monetary transmission mechanism in transition economies: Surveying the surveyable - Ronald MacDonald; Balázs Égert (Magyar Nemzeti Bank, 2006)
This paper surveys recent advances in the monetary transmission mechanism (MTM). In particular, while laying out the functioning of the separate channels in the MTM, special attention is paid to exploring possible interrelations between different channels through which they may amplify or attenuate each others' impact on prices and the real economy. We take stock of the empirical findings especially as they relate to countries in Central and Eastern Europe, and compare them to results reported for industrialised countries, especially for the euro area. We highlight potential pitfalls in the literature and assess the relative importance and potential development of the different channels.
Keywords: E31; E51; E58; F31; O11; P20; 330; monetary transmission; transition; Central and Eastern Europe; credit channel; interest rate channel; interestrate pass-through; exchange rate channel; exchange rate pass-through; asset price channel; Geldpolitische Transmission; Geldpolitische Transmission; Exchange Rate Pass-Through; Geldpolitik; Systemtransformation; Osteuropa